Students' Speaking Skills Using the Show and Tell Method in Lessons - Hasibuan, Masmelan; Siregar, Lis Yulianti Syafrida; Lubis, Maulana Arafat (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
Speaking skills are an important aspect of the communication and learning process, especially at the elementary school level. However, there are still many students who show low speaking skills, characterized by a lack of confidence, limited vocabulary, and dominance of lecture methods in learning. This research aims to improve the speaking skills of grade IV students of SD Negeri 0216 Aek Tunjang through the application of the Show and Tell method in PPKn subjects. Data were collected through observation, interviews, documentation, and speech skills assessments, then analyzed descriptively, quantitatively, and qualitatively. The results showed a significant improvement in students' speaking skills, with the average score increasing from 13% in the pre-cycle to 78.66% in the second cycle and the completeness of classical learning reaching 83.33%. These findings show that the Show and Tell method is effective in building confidence, expanding vocabulary, and encouraging students' active participation in conveying ideas in a concise and clear manner. Therefore, this method is recommended as an effective learning strategy to improve speaking skills in elementary school.